2020
DOI: 10.11591/ijece.v10i6.pp5917-5922
|View full text |Cite
|
Sign up to set email alerts
|

Sentiment analysis of comments in social media

Abstract: Social media platforms are witnessing a significant growth in both size and purpose. One specific aspect of social media platforms is sentiment analysis, by which insights into the emotions and feelings of a person can be inferred from their posted text. Research related to sentiment analysis is acquiring substantial interest as it is a promising filed that can improve user experience and provide countless personalized services. Twitter is one of the most popular social media platforms, it has users from diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 9 publications
0
8
0
3
Order By: Relevance
“…Analisis sentimen ialah pengolahan bahasa natural yang berperan menganalisis pendapat dan juga dapat diartikan sebagai suatu pandangan, keadaan serta perilaku seseorang dalam tulisan ataupun lisan mereka [6]. Analisis sentimen juga dapat sebagai perilaku serta emosi seseorang terhadap suatu produk, penilaian, evaluasi, organisasi, kejadian ataupun topik tertentu [7]. Data itu membagikan informasi untuk bisa membantu seseorang ataupun organisasi dalam pengambilan kesimpulan [8].…”
Section: Gambar 1 Alur Penelitian a Analisis Dataunclassified
“…Analisis sentimen ialah pengolahan bahasa natural yang berperan menganalisis pendapat dan juga dapat diartikan sebagai suatu pandangan, keadaan serta perilaku seseorang dalam tulisan ataupun lisan mereka [6]. Analisis sentimen juga dapat sebagai perilaku serta emosi seseorang terhadap suatu produk, penilaian, evaluasi, organisasi, kejadian ataupun topik tertentu [7]. Data itu membagikan informasi untuk bisa membantu seseorang ataupun organisasi dalam pengambilan kesimpulan [8].…”
Section: Gambar 1 Alur Penelitian a Analisis Dataunclassified
“…This poses a significant The proposed study presents a novel framework for sentiment analysis towards the COVID-19 vaccines based on the tweets. However, various research works on the similar context of sentiment analysis based on social media data are presented in the recent literature [6], [7]. In a similar direction, the authors in [8] collected the tweets over 3 weeks from the European continent to study the increasing impact of the coronavirus.…”
Section: Introductionmentioning
confidence: 99%
“…Kilani et al suggested a hybrid RS [24] based genetic algorithm using MF and KNN that uses both latent factor and neighborhood data to recommend items to an active user. In literature it is shown that ensemble models [25], [26] works better in text-based analytics [27]- [29], intrusion detection [30] and in classification of sounds signals [31].…”
Section: Introductionmentioning
confidence: 99%